Cerebrospinal fluid monoamines, pterins, and folate in patients with mitochondrial diseases: systematic review and hospital experience. Issue 6 (4th July 2018) - Batllori, Marta; Molero‐Luis, Marta; Ormazabal, Aida; Montero, Raquel; Sierra, Cristina; Ribes, Antonia; Montoya, Julio; Ruiz‐Pesini, Eduardo; O'Callaghan, Mar; Pias, Leticia; Nascimento, Andrés; Palau, Francesc.; et al.
Abstract: Mitochondrial diseases are a group of genetic disorders leading to the dysfunction of mitochondrial energy metabolism pathways. We aimed to assess the clinical phenotype and the biochemical cerebrospinal fluid (CSF) biogenic amine profiles of patients with different diagnoses of genetic mitochondrial diseases. We recruited 29 patients with genetically confirmed mitochondrial diseases harboring mutations in either nuclear or mitochondrial DNA (mtDNA) genes. Signs and symptoms of impaired neurotransmission and neuroradiological data were recorded. CSF monoamines, pterins, and 5‐methyltetrahydrofolate (5MTHF) concentrations were analyzed using high‐performance liquid chromatography with electrochemical and fluorescence detection procedures. The mtDNA mutations were studied by Sanger sequencing, Southern blot, and real‐time PCR, and nuclear DNA was assessed either by Sanger or next‐generation sequencing. Five out of 29 cases showed predominant dopaminergic signs not attributable to basal ganglia involvement, harboring mutations in different nuclear genes. A chi‐square test showed a statistically significant association between high homovanillic acid (HVA) values and low CSF 5‐MTHF values (chi‐square = 10.916; p = 0.001). Seven out of the eight patients with high CSF HVA values showed cerebral folate deficiency. Five of them harbored mtDNA deletions associated with Kearns‐Sayre syndrome (KSS), one had a mitochondrial point mutation at the mtDNA ATPase6 gene, and one had a POLG mutation. In conclusion, dopamine deficiency clinical signs were present in some patients with mitochondrial diseases with different genetic backgrounds. High CSF HVA values, together with a severe cerebral folate deficiency, were observed in KSS patients and in other mtDNA mutation syndromes.